How hot is too hot?: Some considerations regarding temperature and performance - Dugas, J. P. (International Journal of Sports Physiology and Performance, 2010)
The regulation of temperature during exercise is a widely debated topic. Two primary views exist, with one embracing a peripheral approach and the other adopting a more integrative and central explanation of the physiology. Especially in the past 10 years, several investigators have published increasingly elegant interpretations that have moved the debate forward.